Factors determining Pokémon Go addiction in Malaysia - Abdul Wahab, Siti Aminah; Jamalludin, Nur Hafifah; Wok, Saodah (Global Academy of Training & Research (GATR) Enterprose, 2017)
This study focuses on factors determining Pokémon Go addiction behaviour among players in Malaysia. Using the Personal Construct Theory (PCT), the relationship between perception of Pokémon Go players and their addiction behaviour toward the game is examined. The objectives of this study are (1) to identify the levels of perception and addiction behaviour of the Pokémon Go players in Malaysia; (2) to determine the relationship between perception and addiction behaviour of the Pokémon Go players; and (3) to investigate the moderating effects of age, gender and ethnicity on the relationship between perception and addiction behaviour of the Pokémon Go players. The study employs quantitative research design. The data were collected from 270 respondents using a self-administered questionnaire. The results show that even though the addiction behaviour of Pokémon Go players is low, the perception of Pokémon Go players towards the game is positive. Therefore, both addiction behaviour and perception are positively related. Age and gender are found to be moderate in the relationship between perception and addiction behaviour. With these results, the assumptions of PCT hold true.